Comparação de métodos para quebra de dormência das sementes de carvoeiro: Tachigali vulgaris L.F. Gomes da Silva e H.C. Lima (Família: Fabaceae - Caesalpinioideae) - Pilon, Natashi Aparecida de Lima [UNESP]; Melo, Antonio Carlos Galvão de; Durigan, Giselda (My University, 2012)
The cultivation of native plants, either for economic exploitation, for ecological restoration or any other purpose, depends, above all, on the possibility of propagation of the species. The production of nursery-raised seedlings is the usual technique for propagation of tree species and seed germination is a critical step for that. The carvoeiro, Tachigali vulgaris, is a woody species of rapid growth and large size, with potential for timber, whose seeds have tegumentary dormancy, impairing the production of seedlings. Searching for the most effective technique to break dormancy of seeds, we compared five treatments with five replications each: control, mechanical scarification (sandpaper 80), immersion in water at room temperature (24 hours), mechanical scarification with sandpaper + immersion in water at room temperature, and immersion during two hours in concentrated sulfuric acid. Most seeds germinated in the first seven days after treatment application, ceasing the emergence of seedlings from this time. The germination rates of untreated seeds or simple immersion in water at room temperature were very low, less than 25%. The germination rates after mechanical scarification with sandpaper (84%), mechanical scarification with sandpaper + immersion in water (72%) and acid scarification (71%) did not differ significantly. Therefore, for the production of seedlings of the species, mechanical scarification of the seeds with sandpaper is recommend, which provides the tegumentary dormancy breaking and does not require chemical treatment.

O cultivo de plantas nativas seja para a exploração econômica, para restauração ecológica ou qualquer outra finalidade, depende, antes de tudo, da possibilidade de propagação das espécies. A produção de mudas é o meio usual de propagação de plantas, considerando-se fundamental a germinação das sementes. Tachigali vulgaris é uma espécie arbórea de crescimento rápido e grande porte, com potencial madeireiro, cujas sementes apresentam dormência tegumentar, que dificulta a produção de mudas. Buscando encontrar a técnica mais eficaz para quebra de dormência de suas sementes, foram comparados cinco tratamentos com cinco repetições: controle, escarificação mecânica, imersão em água em temperatura ambiente (24 horas), escarificação mecânica + imersão em água em temperatura ambiente e escarificação ácida por imersão em ácido sulfúrico concentrado durante duas horas. Quase todas as sementes germinaram dentro de sete dias após a instalação do teste. As sementes sem tratamento ou imersas em água em temperatura ambiente durante 24 horas apresentaram porcentagem de germinação muito baixa, inferior a 25%. A germinação obtida para os tratamentos escarificação mecânica com lixa no 80 (84%), escarificação mecânica + imersão em água (72%) e escarificação ácida (71%) não diferiram significativamente entre si. Para a produção de mudas da espécie, portanto, recomenda-se a escarificação mecânica das sementes com lixa, pelo bom resultado de germinação e por dispensar o tratamento químico.
Comparison of methods for breaking seed dormancy of carvoeiro: Tachigali vulgaris L.F. Gomes da Silva and H.C. Lima (Family: Fabaceae – Caesalpinioideae)
Keywords: Forest species; Germination; Tachi-branco; Espécie florestal; Germinação; Tachi-branco